Hubungan antara Pola Sidik Bibir dengan Jenis Kelamin pada Mahasiswa Fakultas Kedokteran Gigi Universitas Jember (The Correlation between Lip Prints Pattern and Sexual Dimorphism on Students of Faculty of Dentistry, The University of Jember) - Sitti Nur Qomariah; Masniari Novita; Erawati Wulandari (Pustaka Kesehatan, 2016)
Background:Cheiloscopyisaforensicidentificationtechniquesbasedonpatternsofwrinklesandgroovesonthe mucosalsurface ofthelip, calledlipprints. Theunique characteristicsoflipprintsanditsdifferentamonghumanbeingcouldbeusedinidentifypeople.Objective:Theaimofthisstudyistoidentifywhetherthereisacorrelationbetweenlipprintsinsexualdimorphismof studentsofFacultyofDentistry,TheUniversityofJember,ornot.Method:Thedescriptiveobservationalstudyiscrosssectionalapproach.Thesubjectsofthisstudyare80students,comprisingof40malesand40females.Result:Theresultshowedthatthereweredifferenceslipprintspatternbetweenmaleandfemale. Themostdominantlipprint patternin malewastipeIII 16 (40%), whereasthemostdominantlipprintpatterninfemalewastipeI’14(35%).Conclusion:Thedifferencesoflipprintspatternbetweenmaleandfemaleshowedthatlipprintspatterncouldbeused inforensicidentification.Keywords:forensicidentification,lipprintspattern,sexualdimorphism